Pemanfaatan Tepung Daun Cabe-cabe (Lepidagathis javanica) dalam Ransum Terhadap Performan Ayam Broiler - Ucop Haroen (Jurnal Agripet, 2008)
The effect of cabe cabe leaf (Lepidagathis javanica) in feed on broiler performanceABSTRACT. This study was conducted to determine the effect of using cabecabe leaf (Lepidagathis javanica) into the ration on broiler performance. Design of this experiment was assigned to Completely Randomized Design (CRD) in 4 treatments and 5 replications. Each replication contained 5 chickens. The treatments were R0 = basal ration (as control), R1 = 97.5% of basal ration + 2.5% of cabe cabe leaf, R2 = 95.0% of basal ration + 5.0% of cabe cabe leaf and R3 = 92.5% of basal ration + 7.5% of cabe cabe leaf. Basal ration composed by corn, rice bran, soybean meal, coconut meal, fish meal, coconut oil, mineral mix and premix. Parameter measured was feed consumption, daily weight gain and feed conversion ratio. To determine the effect of treatment on the parameter was analyzed by analysis of variance (ANOVA) and the significant effect of treatment on the parameter was analyzed by Duncans Multiple Range Test (DMRT). Result of this study showed that using cabe cabe leaf into the ration significantly (P0.05) decreased feed consumption. Daily weight gain and feed conversion ratio. Duncans Multiple Range Test showed that feed consumption and daily weight gain were significant (P0.05) different between control and all level of cabe cabe leaf, however, feed conversion ratio was significant (P0.05) different only between control and 7.5% of cabe cabe leaf in the ration. It is concluded that using 2.5% of cabe cabe leaf into the ration reduced feed consumption and daily weight gain but not influenced feed conversion ratio up to 5% of using cabe cabe leaf into the ration.